A Comparison of the Effect of Platelets and Erythrocytes on the Inhibitory Action of Blood Coagulation by Polybrene and Heparin - Shanberge, J. N; Furuta, S (Thrombosis and Haemostasis, 1964)
Although the inhibitory action of Polybrene and heparin on blood coagulation in vitro is inversely proportional to the number of platelets present, the reason for this in each case is different. Whereas heparin is counteracted by a substance present in platelets, the platelet factor 4, Polybrene is partially neutralized by adsorption onto the surface of the platelets.Under similar conditions Polybrene is adsorbed by erythrocytes while heparin is not.Platelet factor 4 not only is not anti-Polybrene but, like Polybrene, is also inhibitory in the intermediate product I formation test so that the two together have a greater inhibitory action than either one alone.